(NkAMERNYE INTRUMENTALXNYE PROIZWEDENIQ d(B.(N{OSTAKOWI^A(B.s (Nu^EBNOE POSOBIE(B.s - (Na(B.(Nn(B.(NdOLVANSKIJs ((NsANKT(B-(NpETERBURG(B.s (NlANX(B.s (NpLANETA MUZYKA(B.s, 2024)
(NkAMERNAQ INSTRUMENTALXNAQ MUZYKA QWLQETSQ WAVNOJ PO ZNA^IMOSTI OBLASTX@ TWOR^ESTWA d(B.(Nd(B.(N{OSTAKOWI^A(B.s
Keywords: (NMONOGRAFIQs